Weekend tourism of Košice residents considering the new way of spending free time in entertainment shopping centers - Mitríková Jana; Menyhértová Ivana (Journal for Geography, 2008)
Weekend tourism represents the mass participation of residents in tourism. Košice has the greatest potential for the development of weekend tourism and many opportunities for utilization in the field of historical-cultural monuments, social events, and the expansion of the network of administrative institutions. In 2013, Košice will be the European Capital of Culture, with many projects being realized in the field of culture and tourism, aiming to attract not only domestic but also foreign visitors. Spending leisure time in large retail stores, especially in entertainment shopping centers that offer a combination of many shops and a wide range of services, has become an increasingly popular weekend activity in recent times.